New developments in productivity measurement and analysis - Kendrick, John W.; Vaccara, Beatrice N.; National Bureau of Economic Research (Chicago ; London : University of Chicago Press, 1980)
This volume contains the papers presented at the Conference on New Developments in Productivity Measurement and Analysis held at Williamsburg, Virginia, on 13-14 November 1975. The book is divided into four. I. Labor and Multifactor Productivity by Industry. II. Productivity in Selected Service Sectors. III. The Effects of Research and Development, Energy, and Environment on Productivity. IV. International Comparisons of Productivity
Includes bibliographical references and index.
rpm 19/02/2018
Loans
Keywords: Industrial productivity; Productivity accounting